indonesia PENDIDIKAN MULTIKULTURAL SEBAGAI FONDASI PENGUATAN NILAI-NILAI KEBERAGAMAN DALAM PERSPEKTIF ISLAM: bahasa indonesia - Tedy Dwi Cahyadi; Shuhaib Arumi; Husnul Amaliyah; Putri Rizki Utami; Fatmawaty (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
Indonesia is a country with a rich diversity of ethnicities, cultures, languages, and religions. This diversity requires an educational approach that fosters mutual respect to prevent social conflict. However, reality shows that intolerance, discrimination, social prejudice, and a lack of understanding of diversity persist in society. This article aims to examine multicultural education as a foundation for strengthening the values ​​of diversity and explain its relevance from an Islamic perspective. The method used is library research with a qualitative-conceptual approach. The results of the study indicate that multicultural education is able to instill the values ​​of tolerance, justice, respect for differences, and social cooperation. These values ​​are deeply aligned with Islamic teachings, particularly the values ​​of ta'aruf (community), tasamuh (community to one another), ukhuwah (brotherhood), ta'awun (community to one another), and al-'adalah (the principle of unity). Thus, multicultural education plays a foundation in forming a harmonious, inclusive, and just society in accordance with the spirit of Islam rahmatan lil 'alamin (blessing for the universe).